Formulation and Physical Evaluation of Hydrogel Extract Combination of Centella asiatica and Moringa oleifera using Simplex Lattice Design Method - B Muchtaromah; A F Majid; H Aqila; A Hayati; M M Rehan (IOP Publishing, 2026)
Indexed by SCOPUS